Nové objevy v Petzoldových jeskyních v Českém krasu - Mengler, Z.; Vlk, L.; Záviška, M.; Žák, K. (Karel) (2011)
Cryogenic cave carbonates (CCC) are formed in caves during freezing of calcium bicarbonate water by expulsion of the dissolved load in form of carbonate crystals. Fine-grained (powder) CCC types are formed in recently iced caves by freezing of a thin water layer on the surface of ice. Coarse-grained types, with crystals and crystal aggregates, were formed by slow freezing of water in pools. They were formed within the former permafrost zone during the glacials. The history of CCC discovery is briefly reviewed in the paper, together with the description of three new localities in the Czech Republic and two new localities in Slovakia. Based on the occurrence of CCC, the Glacial minimum permafrost depth can be estimated at 30 m in the Bohemian Karst. The CCC locality discovered in the Mesačný Tieň Cave in Vysoké Tatry Mts. in Slovakia is so far the deepest known CCC site (–285 m under the nearest surface, –195 m below the cave entrance).